Enhancing Analytical Thinking and Scientific Attitude: The 7E Learning Cycle with Socio-Scientific Issues Context in Salt Hydrolysis - Wiqy Mufarrihaturrahma Mustaqimal Hikam; Dyah Purwaningsih (FKIP Universitas Lampung, 2026)
The low level of higher-order thinking skills of students in learning chemistry indicates that students still frequently experience difficulties in developing their thinking abilities. One of the factors is the obstacles in conceptual reasoning and misconceptions experienced by students. These obstacles not only impact the cognitive aspect but are also accompanied by issues in the affective aspect, one of which is a scientific attitude. This serves as an internal factor for establishing optimal learning. One alternative is instruction that uses contexts relevant to daily life, such as implementing the 7E learning cycle model within a socio-scientific issues (SSI) context in learning chemistry. This study aims to examine the effectiveness of the 7E learning cycle model, contextualized with SSI, on students' analytical thinking skills and scientific attitudes regarding salt hydrolysis. The research method used was a quasi-experimental pretest-posttest control group design. The study population included all eleventh-grade students in senior high schools in Madiun City. Sample classes were determined using cluster random sampling, with two experimental and two control classes, for a total of 131 students. The results showed an improvement in students' analytical thinking skills, with an N-Gain score of 0.50, which falls in the medium category, while the improvement in scientific attitude was also in the medium category, with an N-Gain score of 0.35. The MANOVA results showed a significance value of 0.000 < 0.05, indicating a significant difference between the experimental and control groups. The 7E learning cycle, contextualized with SSI, provided a simultaneous, effective contribution of 20.8% to students' analytical thinking skills and scientific attitudes. Based on these findings, it can be concluded that the 7E learning cycle model, contextualized with SSI, has the potential to be more effective in improving students' analytical thinking skills and scientific attitudes regarding salt hydrolysis. Keywords: 7E learning cycle, socioscientific issues, analytical thinking skills, scientific attitude, salt hydrolysis.